Hubungan Tingkat Pengetahuan dan Sikap Masyarakat terhadap Upaya Pencegahan Penyakit Malaria di Kelurahan Dulanpokpok Kecamatan Pariwari Kabupaten Fakfak: The Relationship Between Community Knowledge and Attitudes Toward Malaria Prevention Efforts in Dulanpokpok Village, Pariwari District, Fakfak Regency - Risyanto, Chusnul Aulia Arisny Putri; Armiyanti, Yunita; Hermansyah, Bagus; Rachmawati, Dwita Aryadina (Perkumpulan Entomologi Kesehatan Indonesia, 2024)
Indonesia ranks second in Southeast Asia for the highest number of malaria cases. High endemicity areas are primarily in Eastern Indonesia, including Fakfak Regency in West Papua Province. Malaria is transmitted by Anopheles mosquitoes, and vector control plays a vital role in prevention, especially with challenges such as drug resistance and the lack of a widely applicable vaccine. Malaria cases in Fakfak Regency remain high, possibly due to inadequate community prevention efforts. These efforts are influenced by knowledge and attitudes. This study aimed to examine the relationship between knowledge, attitudes, and malaria prevention efforts in Dulanpokpok Village, Pariwari District, Fakfak Regency. The research employed an observational analytic method with a cross-sectional design, involving 100 respondents. Data were collected through questionnaires on sociodemographics, malaria knowledge, and attitudes, alongside observations of prevention practices. The Spearman Rho test revealed a significant positive correlation between knowledge and prevention efforts (p < 0.05; r = 0.227). However, no significant relationship was found between attitudes and prevention efforts (p > 0.05). The findings suggest that knowledge and attitudes alone are insufficient without concrete prevention actions. Continuous education and monitoring are needed to enhance community efforts in combating malaria effectively.